Identification of the carotenoid cleavage dioxygenase genes and functional analysis reveal DoCCD1 is potentially involved in beta-ionone formation in Dendrobium officinale - Wang, Yue; Xu, Jianchu; Liu, Aizhong (Frontiers in Plant Science, 2022)
The carotenoids are the most widely distributed secondary metabolites in plants and can be degraded by carotenoid cleavage dioxygenase (CCD) to form apocarotenoids including an important C13 compound beta-ionone. Volatile beta-ionone can confer the violet and woody fragrance to plant essential oils, flowers, fruits and vegetables, which therefore has been used in various industries. Dendrobium officinale is a traditional medicinal plant. However, there was limited information on the key enzymes involved in the biosynthesis of beta-ionone in D. officinale. In the present study, beta-ionone was detected in stems and leaves of D. officinale and genome-wide identification and expression profiles of CCD genes were subsequently carried out. There were nine DoCCD members in D. officinale. According to the phylogenetic relationship, DoCCD proteins were classified into six subfamilies including CCD1, CCD4, CCD7, CCD8, nine-cis-epoxycarotenoid dioxygenase (NCED) and zaxinone synthase (ZAS). DoCCD genes showed distinctive expression profiles and DoCCD1 gene was abundantly expressed in eight tissues. Induced expression of DoCCD1 gene resulted in discoloration of Escerichia coli strains that can accumulate carotenoids. Analysis of Gas Chromatography/Mass Spectrometer showed that DoCCD1 enzyme can cleave lycopene to produce 6-methyl-5-hepten-2-one and pseudoionone and also catalyze beta-carotene to form beta-ionone. Expression of DoCCD1 gene in tobacco leaf resulted in production of abundant beta-ionone. The present study first provides valuable information on the CCD gene family, function of DoCCD1 gene as well as production of beta-ionone through genetic modification.